Kolaborasi Pemerintah Desa dan Sekolah Dasar dalam Mewujudkan Sekolah Inklusif di Kecamatan Langgikima, Kabupaten Konawe Utara - Nashar, Abdul; L.Parisu, Chairan Zibar; Brata, Tri (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The condition of inclusive education in rural areas, especially in Langgikima District, North Konawe Regency, still faces various challenges, ranging from the lack of community understanding of the concept of inclusivity to limited institutional support for children with special needs. This service aims to strengthen collaboration between village governments and elementary schools in realizing inclusive schools that are friendly and open to all children. The method of implementing the activity includes socialization, training, and mentoring carried out in a participatory manner with village officials, teachers, and the community. The results of the activity showed an increase in understanding of stakeholders regarding the importance of inclusive education, as well as the emergence of a joint commitment to support access and educational facilities for children with special needs. In addition, this activity provides real benefits in the form of the formation of a communication forum between schools and village governments as a forum for ongoing coordination. This program is expected to become a collaborative model that can be replicated in other areas with similar conditions.